DEVELOPMENT OF ORGANIZATIONAL CULTURE IN PUBLIC AUTHORITIES - Pokotylo , T.; Smahliuk . , A (Theory and Practice of Public Administration, 2021)
The article considers the development of organizational culture and its impact on ensuring the efficiency of public authorities. Active involvement of employees in the activities of the organization, the ability to stimulate organizational change and reduce resistance to their implementation are no longer purely theoretical problems, they are included in the agenda of civil service reform in Ukraine.Approaches to the definition of “organizational culture” and “organizational change” are analyzed. It is established that organizational culture is a hallmark of each organization and a decisive factor in the success of the whole team, values, norms and patterns of behavior and management style can be directly or indirectly reflected in such important elements of public servants as: efficiency, competence, competitiveness, innovation, professionalism, professionalism, quality of service to citizens-consumers of administrative services, teamwork, care for employees, etc.The paper presents the main characteristics of organizational culture, identifies external and internal factors influencing its formation and developed a structural model of organizational culture management in public authorities. Emphasis is placed on the role of the change team in the formation of a systemic vision of organizational culture and organizational change. The role of agents of change as a driving force, a valuable resource, and ideologues in the development of a positive organizational culture is revealed. It is determined that changes in organizational culture are very slow and require significant time and effort, as well as high professionalism of managers. The directions of work with the personnel in the ideological plan, formation of team spirit of the organization, training of the personnel and strategic development of effective internal and external communications in the organization are offered.